Användningen av enspråkigt svenska ordböcker i Finland - Nikula, Kristina (Nordiske Studier i Leksikografi, 1997)
This article presents an analys is of the use of Swedish rnonolingual dictionaries by university students in Finland (University of Tarnpere, University of Vaasa, Åbo Akademi University, Österbottens högskola). It seerns that the subject of the studies plays a greater role than the rnother tongue ofthe students (Swedish or Finnish). The report is based on questionnaires in the spring 1997 and is part of a larger project.